Xiaoyaosan Exerts Antidepressant Effect by Downregulating RAGE Expression in Cingulate Gyrus of Depressive-Like Mice - Yan, Weixin; Dong, Zhaoyang; Zhao, Di; Li, Jun; Zeng, Ting; Mo, Chan; Gao, Lei; Lv, Zhiping (Frontiers in Pharmacology, 2021)
Xiaoyaosan (XYS), as a classic Chinese medicine compound, has been proved to have antidepressant effect in many studies, but its mechanism has not been clarified. In our previous studies, we found that chronic stress can induce depressive-like behavior and lead to emotional related cingulate gyrus (Cg) dysfunction, as well as the decrease of neurotrophic factors and the increase of inflammatory related proteins. Therefore, we speculated that XYS may play an antidepressant role by regulating the inflammation related receptor of advanced glycation protein end product (RAGE) to affect the functional connectivity (FC) signal of Cg and improve the depressive-like behavior. In order to verify this hypothesis, we analyzed the FC and RAGE expression in Cg of depressive-like mice induced by chronic unpredictable mild stress (CUMS), and verified it with RAGE knockout mice. At the same time, we detected the effect of XYS on depressive-like behavior, expression of RAGE and the FC of in Cg of mice. The results showed that the FC of Cg of depressive-like mice induced by CUMS was weakened, and the expression of RAGE was up-regulated. The antidepressant effect of XYS is similar to that of fluoxetine hydrochloride, which can significantly reduce the depressive-like behavior of mice and inhibit the expression of RAGE protein and mRNA in Cg, and increase the FC of Cg in mice. In conclusion, XYS may play an antidepressant role by down regulating the expression of RAGE in the Cg of depressive-like mice induced by CUMS, thereby affecting the functional signal and improving depressive-like behavior.